TOURISM AND HOSPITALITY INDUSTRY IN THE YAROSLAVL REGION: STATISTICAL ANALYSIS - Natalia N. Liparteliani (Статистика и экономика)
The statistical analysis of the current situation at the travel services market in Yaroslavl is made. Main problems of statistical accounting in tourism are revealed. Mathematical and statistical methods are used to give the forecast of tourist activities of companies of the hospitality industry.